2014
DOI: 10.1177/1352458514556296
|View full text |Cite
|
Sign up to set email alerts
|

Natalizumab exerts a suppressive effect on surrogates of B cell function in blood and CSF

Abstract: Natalizumab impacts B and T cell distribution and exerts an inhibitory effect on surrogates of B cell function in periphery and in cerebrospinal fluid, potentially contributing to the increased risk of developing PML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 42 publications
6
53
0
1
Order By: Relevance
“…The IgG CSF/serum ratio increased after PLEX in most cases (anti‐Yo and anti‐Hu). In natalizumab‐treated MS patients treated by PLEX in relation with a progressive multifocal encephalopathy (PML), IgG index increased34 and the activity index (AI) against JCV increased 4‐fold 35. Although a rebound of local IgG synthesis induced by PML‐immune reconstitution inflammatory syndrome (IRIS) could not be excluded, these results are in line with the predicted outcome of ITS after PLEX.…”
Section: Discussionsupporting
confidence: 53%
“…The IgG CSF/serum ratio increased after PLEX in most cases (anti‐Yo and anti‐Hu). In natalizumab‐treated MS patients treated by PLEX in relation with a progressive multifocal encephalopathy (PML), IgG index increased34 and the activity index (AI) against JCV increased 4‐fold 35. Although a rebound of local IgG synthesis induced by PML‐immune reconstitution inflammatory syndrome (IRIS) could not be excluded, these results are in line with the predicted outcome of ITS after PLEX.…”
Section: Discussionsupporting
confidence: 53%
“…A decrease from pretreatment levels in the CD4+/CD8+ ratio in CSF was also observed in a separate longitudinal prospective study of natalizumab-treated patients [Stüve et al 2006]. Moreover, the proportion of CD19+ B cells in CSF has been shown to be lower in natalizumabtreated MS patients (n = 59) than in those not treated with natalizumab (n = 17) [Warnke et al 2015]; whereas increases in mature CD19+ B cells and CD19+, CD10+ pre-B cells in peripheral blood of natalizumab-treated patients were greater than increases in the total peripheral lymphocyte population [Krumbholz et al 2008]. Maoz et al [2014], Politis et al [2013] 1 Politis et al [2013] Increased total N-acetylaspartate, creatine, phosphocreatine and glutamate in lesional white matter relative to pretreatment levels In addition to its effects on CSF cell counts and OCBs, natalizumab affects other markers of inflammation in the CSF and plasma.…”
Section: Effects On Cns Cellular Infiltration and Intrathecal Antibodmentioning
confidence: 77%
“…In studies of CSF profiles in RRMS patients treated with natalizumab for at least 1 year, reductions were seen in CSF levels of CD4+ T cells, B cells (especially CD5+) and OCBs (IgM, and to a lesser extent, IgG) [Mancuso et al 2014;Villar et al 2012;Harrer et al 2013]; whereas OCBs reappeared in the CSF of patients who discontinued natalizumab [Harrer et al 2013;von Glehn et al 2012]. Similarly, a longitudinal study revealed that the CSF CD4+/CD8+ ratio, IgG and IgM levels and IgG-CSF index declined in samples collected during natalizumab treatment compared with pretreatment [Warnke et al 2015]. A decrease from pretreatment levels in the CD4+/CD8+ ratio in CSF was also observed in a separate longitudinal prospective study of natalizumab-treated patients [Stüve et al 2006].…”
Section: Effects On Cns Cellular Infiltration and Intrathecal Antibodmentioning
confidence: 97%
“…36 Notwithstanding the increase in circulating B cells, there is decreased B-cell activity within the CNS compartment during natalizumab therapy. There are fewer B cells detectable in the cerebrospinal fluid (CSF) of natalizumab-treated compared with untreated patients with MS. 37 The CSF-restricted oligoclonal bands indicate excess humoral immunity in the CNS compartment and are present in more than 90% of patients with MS. Once present, they typically persist throughout the lifetime of the disease. Of interest, natalizumab decreases or eliminates CSF-restricted oligoclonal bands in 16% to 55% of patients.…”
mentioning
confidence: 99%